TINJAUAN HUKUM ISLAM TERHADAP UNDANG-UNDANG BIDANG KESEHATAN - Fitra Mulyawan; Kiki yulinda (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
In the development of Indonesian National Law, the existence of Islamic law is very important, in addition to being a material for the preparation of national law, Islamic law is also an inspiration and dynamic in the development of national law. Likewise in the health sector, where the existence of Islamic law is an integral part of national law in the rules that exist in the health sector law. Intended to see whether Islamic law becomes an integral part of the rules in the field of health. Then whether the existence of Islamic law in these rules is explored from Islamic law which develops normatively into positive law. Therefore, Islamic law in the form of fatwas has a strong influence on the legislative process in Indonesia. All of this is clearly seen in the rules of health, first revealed elements of Islamic law that exist in the rules of health, namely the health law from independence to existing laws and apply to this day. So that the health law found a value system in Islam related to health, such as forbidden abortion, the existence of strict rules.